2020
DOI: 10.1007/s10151-020-02372-w
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic negative-pressure wound therapy after ileostomy reversal for the prevention of wound healing complications in colorectal cancer patients: a randomized controlled trial

Abstract: Background The aim of this study was to assess the usefulness of protective negative-pressure wound therapy (NPWT) in the reduction of wound healing complications (WHC) and surgical site infections (SSI) after diverting ileostomy closure in patients who underwent surgery for colorectal cancer. Methods In this prospective randomized clinical trial in a tertiary academic surgical center, patients who had colorectal cancer surgery with protective loop ileostomy and were scheduled to undergo ileostomy closure wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Recently, Wierdak et al demonstrated in a randomized controlled trial that utility of ciNPWT after ileostomy closure in colorectal cancer patients reduces the incidence of wound healing complications and surgical site infection [ 43 ]. Such promising outcomes may have significant implications regarding early stoma reversal surgery, even before adjuvant chemotherapy in colorectal cancer patients as suggested by Kłęk et al [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wierdak et al demonstrated in a randomized controlled trial that utility of ciNPWT after ileostomy closure in colorectal cancer patients reduces the incidence of wound healing complications and surgical site infection [ 43 ]. Such promising outcomes may have significant implications regarding early stoma reversal surgery, even before adjuvant chemotherapy in colorectal cancer patients as suggested by Kłęk et al [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a few studies assessed the effect of NPWT application after loop ostomy closure [8][9][10]. A recently published randomized controlled study of NPWT in primarily closed wounds after loop ileostomy closure described a iSSI rate of 5.7% in the NPWT group vs. 19% without NPWT [9].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a few studies assessed the effect of NPWT application after loop ostomy closure [8][9][10]. A recently published randomized controlled study of NPWT in primarily closed wounds after loop ileostomy closure described a iSSI rate of 5.7% in the NPWT group vs. 19% without NPWT [9]. The present series revealed a similar rate of iSSI in the NPWT group, but lower rates in the control group, which may explain the lack of signi cant difference in the present comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-use negative-pressure wound therapy (NPWT) may represent a strategy to reduce the SSI rate while shortening healing times compared with conventional wound dressing. Previous randomized studies were focused on patients with either inflammatory bowel disease or cancer, and led to conflicting results 16 , 17 . Moreover, these trials failed to assess important patient-related outcomes, such as pain, aesthetic satisfaction and quality of life.…”
Section: Introductionmentioning
confidence: 99%